Madagascar au XXIe siècle : la politique de sa géographie - Hervé Rakoto Ramiarantsoa (EchoGéo)
From the humanist and ecological Republic wished for by President Ratsiraka to the rapid and sustainable development advocated by Marc Ravalomanana, the question of development, major for Madagascar, classified among the Highly Indebted Poor Countries, is henceforth linked to environmental concerns. This orientation has accompanied the Madagascan choice to embark on the proposals of the World Bank, since the 1980s, and is outlined by priority issues such as good governance, sustainable development, and struggle against poverty. In the same time, Madagascar intends to carry on the policy of its geography to achieve this commitment. Does the country do well out of it? Through a reflection on the different policies set up for agriculture and environment, two central issues in the development of a rural country, the paper analyses the tensions resulting from interferences at different levels (local realities, national decisions, supra national injunctions) with which the notions of development and environment are connected. It brings out the lack of a society plan which clearly links up these different scales so that, beyond the booster paradigm of sustainable development, the environment be at the service of the Madagascan territory and society.